PS2:28 Autoantibody profiling in prostvac and ipilimumab treated prostate cancer patients reveals potential biomarkers of immune-related adverse events. (21st March 2018) - Budde, P; Marte, J; Zucht, H-D; Bhandari, S; Tuschen, M; Schulz-Knappe, P; Gulley, J; Heery, C; Madan, R; Schlom, J
Abstract : Purpose: Autoantibodies (AAB) targeting self-antigens can be found in two clinically and immunologically opposing diseases, autoimmune diseases and cancer. While in autoimmune diseases, the immune system is hyperactivated against self-antigens, many tumours suppress the anti-tumour immune response. The therapeutic cancer vaccines PSA-Tricom (Prostvac) is designed to generate an antigen-specific tumour response in metastatic castration-resistant prostate cancer (mCRPC), which is in phase 3 testing. To further augment the immune response, combination therapies of Prostvac with ipilimumab are currently tested in clinical studies. Ipilimumab is an antibody that blocks the immune checkpoint molecule cytotoxic T-lymphocyte-associated antigen 4 (CTLA-4). However, treatment with ipilimumab is associated with immune-related adverse events (irAEs). 1 Since there are no biomarkers for predicting irAEs, we investigated AAB profiles as biomarkers associated with irAE in mCRPC patients treated with prostvac and ipilumumab combination therapy. Methods: Serum samples from 24 mCRPC patients treated with prostvac and ipiliumab therapy were tested for the presence of serum autoantibodies against 842 preselected antigens. Candidate antigens comprise immune-related and cancer signalling pathway proteins, autoimmune disease antigens, and tumor-associated antigens (TAA). Samples were collected prior to treatment (T0 samples), at 3 and 6 month. IrAEs included rash, elevated aminotransferases, neutropenia, diarrhoea, colitis and endocrine irAEs. Overall survival was also captured and correlated with AABs. Autoantibody levels were measured by Luminex FlexMap3D bead based multiplex protein arrays 2 and data were analysed by significance analysis of microarrays (SAM), Partial least squares regression (PLS) and Pearson's correlation. Results: In total, 87 AABs were found that were significantly different in patients with irAEs and those without irAEs (SAM |d|>2.5; Pearson's correlation |3|>0.35). PLS analysis revealed that AABs associated with irAEs were also associated with overall survival. Gene ontology analysis of pathways, molecular function and cellular localization revealed that AABs predicting irAEs target cancer, cell cycle, cell adhesion and apoptotic pathways. We also found elevated levels of AABs in patients who do not experience irAEs. Interestingly, these 40 AABs target proteins that are involved in inflammatory, adaptive and cellular immune response pathways or are autoimmune disease antigens. Conclusions: AABs that target antigens involved in cancer signalling pathways are associated with irAEs following prostvac plus checkpoint inhibitor combination therapy. In contrast, AABs targeting immune response pathways were found in patients who do not develop iRAEs and may counteract the action of inflammatory molecules. Similarly, anti-cytokine AABs have been found in autoimmune diseases, were they appear to counteract the pathological effects of cytokines. 3 Further studies in larger sample sets are needed to confirm these findings. References: . Madan RA, et al. Lancet Oncol2012;13(5):501–8. . Budde P, et al. Lupus2016;25:812–22. . Cappellano G, et al. Am J Clin Exp Immunol2012;1(2):136–46.